Care to terminal patients. Perception of nurses from the intensive care unit of a hospital - Mussolin Tamaki, Camila; Meneguin, Silmara; Aguiar Alencar, Rubia; Bronzatto Luppi, Claudia H.elena (My University, 2014)
OBJECTIVE: To identify the perception of nurses with regard to the process of providing care to patients in the context of hospice care. METHOD: Qualitative study using the methodological framework Collective Subject Discourse. A total of 18 nursing professionals of the adult intensive care unit of a public hospital in São Paulo, Brazil were interviewed between June and August 2012. RESULTS: The process of providing care to terminal patients is permeated by negative, conflictive and mixed feelings. As regards communication, while the participants acknowledge its importance as a therapeutic resource, they also admit a lack of professional qualification. CONCLUSION: The interviewees have difficulties to deal with care provided to terminal patients. The qualification of these professionals needs to be improved, starting in the undergraduate program.